Optimasi Kinerja Buck Converter Menggunakan Proportional Integral Controller untuk Regulasi Tegangan Stabil - Ansutia, Muhammad Rinande; Jamaluddin, Jamaluddin; Putera, Perdana (Universitas Trunojoyo Madura, 2025)
Optimization of Buck Converter performance is carried out through the application of a Proportional-Integral (PI) Controller to achieve more stable output voltage regulation in direct current (DC)-based electronic systems. The Buck Converter is a DC-DC converter that steps down the input voltage to a lower output voltage; however, in an open-loop configuration, maintaining output voltage stability becomes challenging when load variations or input fluctuations occur. These conditions lead to regulation errors, overshoot, and oscillations that reduce system accuracy and reliability. In this study, the PI Controller is implemented in a closed-loop configuration as a solution to enhance voltage regulation performance. The research method is conducted entirely through simulations using PLECS software, analyzing system responses under both open-loop (without PI Controller) and closed-loop (with PI Controller) conditions. Simulation results show that the open-loop system is highly dependent on input voltage variations and unable to maintain output voltage consistently at the reference value. In contrast, the PI Controller significantly reduces the steady-state error from an average of 25,13% to 0,52%, accelerates stabilization time, and eliminates excessive overshoot observed in the open-loop system. Additionally, the output voltage can be maintained near 12 V with a maximum deviation of only 0,08 V despite changes in input voltage. These findings demonstrate that the PI Controller is effective in improving stability, accuracy, and reliability of voltage regulation in Buck Converters. The results contribute to the development of power electronics systems requiring more adaptive and efficient voltage control under various operating conditions.